Dynamic Penetration Profile of Starch Betainate, Pluronics and PCC Coated Papers - Sharma, Mohit; Aguado, Roberto; Valente, Artur; Murtinho, Dina; Ferreira, Paulo (KnE Materials Science, 2022)
Despite changes in optical and printing properties, the applied coating components on the paper surface have a significant impact on the surface chemistry of office paper. Depending on the use, such as ink penetration for printing and writing papers, an optimal hydrophobic and hydrophilic balance may be beneficial. In this study, several coating components including starch betainate, Pluronics, and precipitated calcium carbonate were employed to coat base paper (paper without any surface treatment). The influence of these components on water penetration was investigated using dynamic penetration. When compared to native starch coated papers, paper coated with starch betainate (a cationic starch ester) showed reduction in hydrophobicity and increased water penetration. Moreover, this effect was further enhanced with the use of Pluronics. Likewise, hydrophobicity decreased as the concentration of starch betainate, precipitated calcium carbonate and Pluronics increased. Furthermore, water penetrated even more quickly when the combination of these components compared with the individual component coatings. Keywords: hydrophobicity, PCC, Pluronics, starch betainate, water penetration